Involving Children and Teenagers With Bilateral Cochlear Implants in the Design of the BEARS (Both EARS) Virtual Reality Training Suite Improves Personalization - Vickers, Deborah; Salorio-Corbetto, Marina; Driver, Sandra; Rocca, Christine; Levtov, Yuli; Sum, Kevin; Parmar, Bhavisha; Dritsakis, Giorgos; Albanell Flores, Jordi; Jiang, Dan; Mahon, Merle; Early, Frances; et al. (Frontiers in Digital Health, 2021)
Older children and teenagers with bilateral cochlear implants often have poor spatial hearing because they cannot fuse sounds from the two ears. This deficit jeopardizes speech and language development, education, and social well-being. The lack of protocols for fitting bilateral cochlear implants and resources for spatial-hearing training contribute to these difficulties. Spatial hearing develops with bilateral experience. A large body of research demonstrates that sound localisation can improve with training, underpinned by plasticity-driven changes in the auditory pathways. Generalizing training to non-trained auditory skills is best achieved by using a multi-modal (audio-visual) implementation and multi-domain training tasks (localisation, speech-in-noise, and spatial music). The goal of this work was to develop a package of virtual-reality games (BEARS, Both EARS) to train spatial hearing in young people (8–16 years) with bilateral cochlear implants using an action-research protocol. The action research protocol used formalized cycles for participants to trial aspects of the BEARS suite, reflect on their experiences, and in turn inform changes in the game implementations. This participatory design used the stakeholder participants as co-creators. The cycles for each of the three domains (localisation, spatial speech-in-noise, and spatial music) were customized to focus on the elements that the stakeholder participants considered important. The participants agreed that the final games were appropriate and ready to be used by patients. The main areas of modification were: the variety of immersive scenarios to cover age range and interests, the number of levels of complexity to ensure small improvements were measurable, feedback, and reward schemes to ensure positive reinforcement, and an additional implementation on an iPad for those who had difficulties with the headsets due to age or balance issues. The effectiveness of the BEARS training suite will be evaluated in a large-scale clinical trial to determine if using the games lead to improvements in speech-in-noise, quality of life, perceived benefit, and cost utility. Such interventions allow patients to take control of their own management reducing the reliance on outpatient-based rehabilitation. For young people, a virtual-reality implementation is more engaging than traditional rehabilitation methods, and the participatory design used here has ensured that the BEARS games are relevant.